Screening songs in Hispanic and Lusophone cinema : subtitle [delete if appropriate] - Shaw, Lisa, 1966-; Stone, Rob, 1965- (Manchester University Press, 2019)
'In this volume, eighteen experts from a variety of academic backgrounds explore the use of songs in films from the Spanish- and Portuguese-speaking worlds. This volume illustrates how - rather than simply helping to tell the story of - songs in Hispanic and Lusophone cinema commonly upset the hierarchy of the visual over the aural, thereby rendering their hearing a complex and rich subject for analysis. Screening songs ... constitutes a ground-breaking, interdisciplinary collection. Of particular interest to scholars and academics in the areas of Film Studies, Hispanic Studies, Lusophone Studies and Musicology, this volume opens up the study of Hispanic and Lusophone cinema to vital, new, critical approaches. The soundtracks of films as varied as City of God, All About My Mother, Bad Education and Buena Vista Social Club are analysed alongside those of lesser known works that range from the melodramas of Mexican cinema's golden age to Brazilian and Portuguese musical comedies from the 1940s and 1950s. Fiction films are studied alongside documentaries, the work of established directors like Pedro Almodóvar, Carlos Saura and Nelson Pereira dos Santos alongside that of emerging filmmakers, and performances by iconic stars like Caetano Veloso and Chavela Vargas alongside the songs of Spanish Gypsy groups, Mexican folk songs and contemporary Brazilian rap' --Back cover.
Made available via: manchesterhive.
Keywords: Motion picture music -- Spain -- History and criticism.; Motion picture music -- Portugal -- History and criticism.; Motion pictures -- Spain -- History.; Motion pictures -- Portugal -- History.; Film, Musique de -- Espagne -- Histoire et critique.; Film, Musique de -- Portugal -- Histoire et critique.; Cinéma -- Espagne -- Histoire.; Cinéma -- Portugal -- Histoire.; Film, TV and radio.; ART -- Film & Video.; ART / Film & Video; Motion pictures; Motion picture music; Spain; Portugal; The Arts -- Fine arts: art forms -- Non-graphic art forms -- Electronic, holographic & video art.; Electronic books; History; Criticism, interpretation, etc.